An analysis of the causes of factionalism in political parties in Zimbabwe: the case of ZANU PF and MDC from 2005 to 2015. - Mare, Ronald T. (Midlands State University, 2017)
The 21st Century political arena has seen the rise of factionalism in Zimbabwean politics disturbing almost all the political parties in the land, with this phenomenon becoming a topical issue in the media and in political debates. It is therefore the aim of this analytical study to unveil the major causes of factionalism in Zimbabwean political parties with a case study of the two major dominant political parties the ZANU PF and MDC from 2005 to 2015 where these issues started to record a rise and to take an overwhelming interesting direction. The researcher made extensive use of available literature based on newspapers, reports, journals, books and various online articles covering this area of study, which has been backed by field research conducted from the headquarters of these political parties under study in order to achieve unbiased results and authenticate the responding sources. The study has traced the historical development of factionalism and exposed theories of Madison, Harmel, Plato and Hobbes on human nature and factionalism in order to fully understand this phenomenon, done a cost benefit analysis of factionalism to understand its costs and benefits to political parties, highlighted strategies that political parties and their leaders have employed to deal with this phenomenon under study to be able to structure out of these the best progressive strategy, highlighted outcomes and findings of the ground research, shown how political parties can progressively deal with factionalism without splits occurring, unveiled the major cause of factionalism which the research has attributed to human nature as the drive with its tenets of greediness, selfishness and the constant desire to dominate others, predicted the future of Zimbabwean politics as regards this phenomenon and proffered recommendations to help address this cause.